Prevalence and Pattern of Paediatric dermatoses among children in Aminu Kano teaching Hospital Kano, Nigeria - Yahya, Aishatu (Acta Biomedica Atenei Parmensis, 2022)
Introduction: Skin disorders are common among children, most especially the infections and infestations as the immunity is not fully developed during childhood. Skin disorders are among common causes of morbidity in developing countries of Sub-Saharan Africa.Skin disorders are major cause of concern among children. This study aimed to document the prevalence of skin diseases among children who attended the paediatric outpatient clinic of the Aminu Kano Teaching Hospital (AKTH) Kano, Nigeria.Methods: It was a cross-sectional study. The study population included children aged between 6 weeks and 14years from the study area who attend Paediatric Out Patient Department (POPD) clinics recruited consecutively. Data obtained from the patients included age, gender, clinical features, socio-economic class and diagnosis.Result: Two hundred and twenty-three children aged 6weeks to 14years were enrolled into the study. The mean age of the children was 84.42+ 40.12. There were 110 males (49.3%) and 113 females (50.7%) with Male to female ratio 1:1.1. Fifty-five children (24.7%) had skin disorders. There were 14 specific diagnosis made. The leading categories were infections accounting for 18.3% of the skin disorders (p < 0.001). Seborrheic dermatitis was the commonest specific diagnosis found among 3.1% of the children.Conclusion: Prevalence of skin disorders among children attending POPD of Aminiu Kano Teaching Hospital is 24.7%. Infections and infestations were the commonest category of skin disorders found.